Fund management a study of puthukad service co-operative bank LTD NO.580 - Neethu T A (College co-operation, banking and management, 2010)
The study “Fund management – A study of Puthukad Service Co – operative Bank Ltd No. 580” was undertaken to analyze the fund management practices of Puthukad Service Co – operative Bank (PSCB). Ratio analysis covering efficiency in mobilization, deployment and operational efficiency were employed for studying the fund management practices. The ratios were worked out on the basis of secondary data collected from audited annual reports of the bank. The study highlighted that the bank able to attract more deposits during the study period. As a result the dependency of borrowed funds on working capital increased from year to year. But there was not much improvement in the deployment of funds. Only a slight improvement depicted from the study. So the bank should concentrate on the efficient deployment of funds otherwise it adversely affect the spread margin. The bank should take care to increase the non interest income for improvement of profitability.